Assisted eco-driving : a practical guide to the design and testing of an eco-driving assistance system (EDAS) /: a practical guide to the design and testing of an eco-driving assistance system (EDAS). (2021) - Allison, Craig K; Fleming, James M; Yan, Xingda; Lot, Roberto; Stanton, Neville A (Neville Anthony), 1960-
No abstract available